Safety of tocilizumab in COVID‐19 pregnant women and their newborn: A retrospective study. (26th February 2021) - Jiménez‐Lozano, Inés; Caro‐Teller, José Manuel; Fernández‐Hidalgo, Nuria; Miarons, Marta; Frick, Marie Antoinette; Batllori Badia, Emma; Serrano, Berta; Parramon‐Teixidó, Carlos Javier; Camba‐Longueira, Fátima; Moral‐Pumarega, Maria Teresa; San Juan‐Garrido, Rafael; Cabañas Poy, Maria Josep; et al.
Abstract: What is known and objective: Tocilizumab is an IL‐6 receptor inhibitor agent which has been proposed as a candidate to stop the inflammatory phase of infection by the severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2). However, safety data of tocilizumab in pregnant women and their newborn are scarce. We aimed to describe maternal and neonatal safety outcomes associated with tocilizumab treatment in pregnant women with severe COVID‐19. Methods: This is a retrospective study of severe COVID‐19 pregnant women, treated with tocilizumab in two Spanish hospitals between 1 March and 31 April 2020. Demographics, medical history, clinical and radiologic findings, treatment information and laboratory data of mothers and their newborns were collected from electronic medical records. Results and discussion: A total of 12 pregnant women were identified to have received tocilizumab during pregnancy in the two hospitals. Median gestational age at admission was 27.7 weeks (interquartile range, 18.0–36.4). Most of them received lopinavir/ritonavir, azithromycin and hydroxychloroquine, two patients received corticosteroids and one received interferon beta 1B. All 12 pregnancies resulted in live births. Somatometric values were normal for all newborns, and evolution at 14 and 28 days was favourable for all of them. Hepatotoxicity was observed in 2 patients, which improved or resolved at discharge. Cytomegalovirus reactivation was detected in another patient who had also received corticosteroids for 15 days, causing a congenital infection in her newborn. Both hepatotoxicity and viral reactivation adverse events were classified as possibly related to tocilizumab administration according to Naranjo's causality algorithm. What is new and conclusions: It does not appear that tocilizumab has detrimental effects for the mother and newborn. Close monitoring of infections should be considered, especially if other immunosuppressive agents are used. Abstract : Evolution of cytomegalovirus viral load and serology tests in one pregnant patient, in which viral reactivation was detected. She received a single dose of tocilizumab and methylprednisolone therapy for 15 days. Baseline IgM antibodies and amniotic fluid polymerase‐chain‐reaction were negative, but they became positive 6 days after tocilizumab infusion and viral load was detected on day 13.